Notes on spermatophores in Cyphophthalmus duricorius Joseph (Arachnida: Opiliones: Sironidae) - Novak, Tone (Annales. Series historia naturalis, 2005)
The spermatophores in the sironid species Cyphophthalmus duricorius duricorius(Joseph, 1868) are presented. They were found in three females in Slovenia. The spermatophores consist of a bulb-like terminal portion, a tubular, and a basal portion, and are very similar to those in C. serbicus (Hadži, 1973).
Keywords: Arachnida; Opiliones; pajkovci; Sironidae; spermatofor